Oxidation of melatonin by AAPH-derived peroxyl radicals: Evidence of a pro-oxidant effect of melatonin - Ximenes, Valdecir Farias [UNESP]; Pessoa, Adriano S. [UNESP]; Padovan, Camila Z. [UNESP]; Abrantes, Daniele C. [UNESP]; Gomes, Fabiana Helena F. [UNESP]; Maticoli, Michele A. [UNESP]; Menezes, Manoel Lima de [UNESP] (Elsevier B.V., 2009)
Background: Melatonin is well-established as a powerful reducing agent of oxidant generated in the cell medium. We aimed to investigate how readily melatonin is oxidized by peroxyl radicals ROO(-) generated by the thermolysis of 2,2'-azobis(2-amidinopropane) hydrochloride (AAPH) and the role of glutathione (GSH) during the reaction course.Methods: Chromatographic, mass spectroscopy, and UV-visible spectrometric techniques were used to study the oxidation of melatonin by ROO(-) or horseradish peroxidase (HRP)/H(2)O(2). Our focus was the characterization of products and the study of features of the reaction.Results: We found that N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK) and a monohydroxylated derivative of melatonin were the main products of the reaction between melatonin and ROO(-). Higher pH or saturation of the medium with molecular oxygen increased the yield of AFMK but did not affect the reaction rate. Melatonin increased the depletion of intracellular GSH mediated by AAPH. Using the HRP/H(2)O(2) as the oxidant system, the addition of melatonin promoted the oxidation of GSH to GSSG.Conclusions: These results show, for the first time, that melatonin radical is able to oxidize GSH.General significance: We propose that this new property of melatonin could explain or be related to the recently reported pro-oxidant activities of melatonin. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Melatonin; N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK); 2,2 '-azobis(2-methylpropionamidine) dihydrochloride (AAPH); Glutathione; pro-oxidant activity